Environmental and trophic changes through a long-term analysis of the Chantuto-Panzacola Lagoon System, Chiapas, Mexico - Gómez-Ortega, Rocío (2017)
Eutrophication is the enrichment of a water body with nutrients, thus fostering an increase in primary productivity; it is frequently related to proliferation of harmful algae blooms and hypoxia/anoxia conditions. Eutrophication and increased anthropogenic pressure have become a phenomenon of global proportions; consequently, efforts are currently underway for their detection and control. This paper analyses the spatial and temporal variation of the Chantuto-Panzacola estuarine system, based on records of more than two decades (1990-2009) and its current physicochemical condition (2015-2016). Trophic and ecological indexes were applied and developed to tropical conditions, as well as their variation over the period of analysis. Quantification and analysis of physicochemical variables and ecological index determined that there have been changes in the annual pattern of nutrients and trophic index since 2008, mainly determined for nitrates and nitrites. However, during the last year a greater predominance of ammonium was observed. Comparing a little over 25 years, higher concentrations were obtained during the last periods in all nutrients, whose annual average concentrations increased more than 90%. Trophic index corroborated an active process of eutrophication since 2008, with an emphasis on the Chantuto, Los Cerritos and Panzacola lagoons, due to the constant contribution of nutrients from adjacent rivers that contribute to the increase of nitrogen and phosphorus.